Liquid silage of peach (Prunus pérsica) as an alternative in animal feed (2020)
The compositional value and presence of microorganisms in peach liquid silage (Prunus pérsica) were evaluated. A completely randomized design with factorial arrangement 2*2 was applied. Four treatments were determined with two percentages of inclusion of molasses and ammonium sulphate: T1 (10% molasses - 1% SAM), T2 (10% molasses - 3% SAM), T3 (20% molasses - 1% SAM) and T4 (20% molasses - 2% SAM), with three repetitions. They were stored between 17 and 19 ° C. Physical-chemical characterization of the fruit was carried out, pH values ​​were taken, compositional analysis and microbiological growth, bacterial morphology was determined on blood agar and MacConkey agar. The organoleptic evaluation of the final silage is established as GOOD according to fermentative characteristics. The protein value increased in each of the treatments as the pH value decreased, associated with high microbial growths improving the true protein of the food. There was growth of whitish and smooth colonies in blood agar with predominance of bacillary Gram + and Gram -. In MacConkey Agar, pink-colored colonies grew on the smooth surface only on day 0. Liquid peach silage with the addition of SAM increases protein values; and the addition of molasses improves the fermentative parameters as pH stability